2004
DOI: 10.1080/03650340310001627559
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fertilizer experiments as a data base for calculating the carbon sink potential of arable soils

Abstract: Long-term experiments in Mu¨ncheberg, Braunschweig and Livada were used to understand the complex issue of carbon sequestration in soil. The investigations were focused on: effects of land use changes on the fate of soil organic carbon; options of agronomic practices to maintain or to increase soil organic carbon; relationships between organic fertilization and changes in soil organic carbon. The long-term observations showed that the amount of soil organic matter is primarily a function of the prevailing land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Application of FYM to rice and wheat increased organic carbon status of soil (Chettri et al, 2003). Similarly, Rogasik et al (2004) indicated that combination of organic and mineral fertilizes increased soil organic carbon content compared to exclusive mineral fertilizers. Labile carbon content ranged from a minimum of 3.70 mg/kg in no manure treatment and maximum of 5.32 mg/kg in the soil amended with vermicompost.…”
Section: Resultsmentioning
confidence: 91%
“…Application of FYM to rice and wheat increased organic carbon status of soil (Chettri et al, 2003). Similarly, Rogasik et al (2004) indicated that combination of organic and mineral fertilizes increased soil organic carbon content compared to exclusive mineral fertilizers. Labile carbon content ranged from a minimum of 3.70 mg/kg in no manure treatment and maximum of 5.32 mg/kg in the soil amended with vermicompost.…”
Section: Resultsmentioning
confidence: 91%
“…(2) A wide range of management practices had to be pooled in one land‐use class. Several studies have shown that especially agricultural systems comprise numerous management factors such as tillage intensity, type and intensity of manuring, crop type, residue management, crop rotations or length of intertillage periods that might strongly influence SOC dynamics (Liebig et al , 2004; Rogasik et al , 2004; Gál et al , 2007; Sleutel et al , 2007; Angers & Eriksen‐Hamel, 2008; van Wesemael et al , 2010). We found that the management intensity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms a favourable effect of organic with mineral fertilization on the soil organic carbon (Bhattacharyya et al 2010). After liming the soil organic carbon content increased in all the objects, despite the fact that intensive liming can decrease its amount (Rogasik et al 2004).…”
Section: Resultsmentioning
confidence: 99%